Porous carbon, composite material, diaphragm modification material and application thereof
By converting agricultural waste into porous carbon with high specific surface area and loading metal sulfides, materials used for the modification of separators of lithium-sulfur batteries and sodium-sulfur batteries are prepared, and the performance of batteries due to shuttle effects during charging and discharging is solved. The problem of instability has achieved significant improvements in battery performance and safety.
Patent Information
- Application Number
- CN202211656485.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-22
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2042-12-22
AI Technical Summary
During the charging and discharging process, the performance of existing lithium-sulfur batteries and sodium-sulfur batteries is unstable due to the shuttle effect of long-chain polysulfur ions and poor redox reaction kinetics. Moreover, commercial polypropylene separators cannot effectively suppress the shuttle effect, affecting the battery. long cycle stability and rate performance.
Materials for diaphragm modification are prepared by converting agricultural waste into porous carbon with a high specific surface area and loading metal sulfides on its surface. The material is prepared by a carbonization-activation strategy, combining electrostatic adsorption and physical interactions, blocking the shuttle of polysulfide ions and improving catalytic activity and electrochemical properties through the loading of metal sulfides.
It significantly improves the electrochemical performance of lithium-sulfur batteries and sodium-sulfur batteries, extends the cycle life of the battery, enhances the rate performance, and reduces the generation of dendrites by improving the wetting property and ionic conduction of the electrolyte, and improves the battery's Security.
Smart Images

Figure CN116040627B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of energy storage materials, and in particular relates to porous carbon, composite materials, diaphragm modification materials and applications. Background Art
[0002] Organic materials abandoned during agricultural production are called agricultural waste. It is estimated that the amount of agricultural waste is increasing at a rate of 5-10% per year. About 900 million tons of straw agricultural waste are output each year, of which about 200 million tons are not used. The nitrogen and phosphorus production of livestock and poultry waste each year is 1.229×10 7 t and 2.046×10 6 t, but the comprehensive utilization rate is less than 60%.
[0003] Alkali metal sulfur batteries (lithium sulfur batteries, sodium sulfur batteries) have attracted much attention due to their high theoretical capacity and high energy density. However, during the charge and discharge process, the shuttle effect of long-chain polysulfide ions and poor redox reaction kinetics have hindered the commercial development of their batteries. In addition, the pore size of the current commercial polypropylene separator (50-500nm) is much larger than the kinetic diameter of polysulfide ions (>1.6nm), which cannot effectively inhibit the "shuttle effect", thereby affecting the long-cycle stability and rate performance of the sulfur positive electrode. Summary of the invention
[0004] In view of the above shortcomings of the prior art, the present invention provides a porous carbon, a composite material, a diaphragm modification material and its application, which effectively opens up new ways and solutions for the subsequent treatment of agricultural waste, and can be expanded for production. The porous carbon obtained has rich surface active functional groups and has the characteristics of metal-heteroatom co-doping. After further loading metal sulfides, it is used as a diaphragm modification material, which can generally improve the performance of multiple types of secondary batteries. In addition, the solution of constructing a diaphragm modification layer is used to improve the problem of rapid capacity decay caused by the "shuttle effect" in lithium-sulfur and sodium-sulfur batteries, as well as the battery safety problems caused by dendrite growth in other secondary batteries, which has good ecological and economic benefits.
[0005] Through extensive research, the inventors found that by selecting different activators and optimizing technical parameters such as treatment atmosphere, treatment temperature, and feed ratio, the carbonization-activation strategy can be used to convert agricultural waste into carbonized materials with a specific surface area of 800-3500m 2 / g of porous carbon, its hierarchical porous structure can promote the rapid transmission of electrolyte and ions, and use physical interactions such as electrostatic adsorption to block the shuttling of polysulfide ions. In addition, it has a large specific surface area and is an ideal host for catalysts with high catalytic activity. It can effectively inhibit the deactivation of catalysts due to agglomeration or adsorption of a large number of polysulfide ions, and provide a larger reaction interface for the conversion of polysulfide ions, effectively anchor dissolved polysulfide ions to accelerate their catalytic conversion efficiency. And it has a wide range of application value in the fields of catalysis, energy storage, and environmental remediation. 2) Not only that, the inventors found that after the obtained porous carbon material is doped with heteroatoms and loaded with transition metal sulfides, it is possible to simultaneously achieve high-value utilization of resources and improve the performance of alkali metal sulfur batteries. Its electrochemical performance has been further improved, and it has great development advantages. It can be used to prepare diaphragm modification layer materials with good electrochemical properties, accelerate the charge and discharge reaction kinetics, and increase the battery capacity. 3) The membrane modification layer formed after the application of the membrane modification material has rich surface pores and functional groups, good wettability with the electrolyte, good ion conductivity on the interface, and can effectively even out the ion flux and reduce the formation of dendrites. At the same time, since the membrane modification layer has a certain rigidity compared to the polymer membrane, it can effectively avoid the battery short circuit caused by dendrites piercing the membrane, so it also has great application potential in other types of secondary batteries (such as lithium-ion batteries, lithium metal batteries, sodium-ion batteries).
[0006] The present invention specifically provides a porous carbon, which uses agricultural waste as a biomass material, mixes the biomass material with an activator, and places the mixture in a reaction vessel, and performs an activation heat treatment under the protection of an inert gas to obtain the porous carbon;
[0007] The agricultural waste is at least one of silkworm excrement, basswood, mushroom residue, tangerine peel, orange peel, wheat straw, rice straw, corn straw, Miscanthus, and ramie, preferably silkworm excrement;
[0008] The activator is at least one of zinc chloride, phosphoric acid, potassium ferrate, potassium hydroxide, ferric chloride, ferric nitrate and water vapor, preferably potassium hydroxide.
[0009] As a preferred embodiment, the mass ratio of the biomass material to the activator is 1:0.1-6, preferably 1:4; in addition, when potassium ferrate is selected as the activator, the concentration of the potassium ferrate solution is 0.01-0.4M, preferably 0.3M; when zinc chloride is selected as the activator, the concentration of the zinc chloride solution is 1-10M, preferably 5M; when phosphoric acid is selected as the activator, the concentration of the phosphoric acid is 1-85wt%, preferably 50wt%.
[0010] The inert gas is nitrogen, argon or a hydrogen-argon mixture, preferably argon, and the flow rate of the inert gas is 0.1-2L / min, preferably 1L / min; the temperature of the activation heat treatment is 200-1500°C, preferably 800°C, the heating rate is 1-20°C / min, preferably 3°C / min, and the activation heat treatment time is 0.5-10h, preferably 3h.
[0011] As a preferred solution, the agricultural waste needs to be pre-treated, and the pre-treatment steps are washing and drying;
[0012] The cleaning is at least one of water washing, hydrochloric acid washing, sulfuric acid washing, nitric acid washing, hydrofluoric acid washing, sodium hydroxide washing, potassium hydroxide alkaline washing, and ethanol washing, preferably acid washing, more preferably hydrochloric acid washing;
[0013] The drying temperature is 40-150° C., preferably 80° C., and the drying time is 6-72 hours, preferably 48 hours.
[0014] As a preferred solution, depending on the type of agricultural waste, for some agricultural waste with larger particle size, the dried agricultural waste needs to be further crushed and sieved, and the powder particle size after crushing is 50-400 mesh, preferably 100 mesh. For some agricultural waste with smaller particle size, such as silkworm excrement, mushroom residue, etc., there is no need to crush and sieve.
[0015] As a preferred solution, according to the selection of the type of activator, when the activator is easy to react with the impurities (calcium, magnesium, silicon, etc.) coexisting in the biomass material, such as potassium hydroxide, potassium ferrate, etc., the pretreated agricultural waste needs to be pre-carbonized under the protection of an inert gas before mixing with the activator; wherein the inert gas is nitrogen, argon or a hydrogen-argon mixture, preferably argon; the flow rate of the inert gas is 0.1-1L / min, preferably 1L / min; the temperature of the pre-carbonization heat treatment is 200-1500°C, preferably 500°C, the heating rate is 1-20°C / min, preferably 5°C / min, and the pre-carbonization heat treatment time is 0.5-10h, preferably 1h.
[0016] The porous carbon provided by the present invention, the carbonization-activation process, and further coordinated control of the heat treatment process (such as atmosphere, heating rate, treatment temperature, treatment time) and the type and proportion of the added activator can adjust the morphology of the obtained precursor and the specific surface area of the material to improve its electrochemical performance. By changing the type of biomass to be treated, its natural morphology and elemental composition can be used to obtain biomass porous carbon with different physical and chemical characteristics. The inventors have found that in the system of the present invention, the use of an activator can significantly increase the specific surface area of the obtained porous carbon, and the specific surface area of the obtained porous carbon is distributed in the range of 800-3500m 2 / g, combined with the reaction characteristics of different activators, biomass can be converted into a directional carbon lattice that can be embedded in various endogenous non-carbon elements in biomass during thermal treatment or modified on the porous carbon surface in the form of functional groups, which can provide abundant active sites for catalysis and adsorption processes in subsequent applications. By further loading sulfides on porous carbon, its application potential in lithium-sulfur battery catalytic materials can be enhanced.
[0017] The present invention also provides a composite material, wherein the porous carbon and sulfide are mixed in a solvent, the mixture is then vacuum filtered, the filter residue is dried, and annealed under the protection of an inert gas to obtain a porous carbon-sulfide composite material.
[0018] As a preferred embodiment, the sulfide is cobalt disulfide, sodium sulfide, potassium sulfide, zinc sulfide, magnesium sulfide, ferrous sulfide, manganese sulfide, lead sulfide, cadmium sulfide, antimony sulfide, bismuth sulfide, molybdenum sulfide, stannous sulfide, silver sulfide, copper sulfide, nickel sulfide, calcium sulfide, strontium sulfide, barium sulfide, preferably cobalt disulfide; the solvent is ethanol, ethylene glycol, dimethylformamide, ethylene glycol monomethyl ether, butanol, octanol or octyl acetate; the inert gas is nitrogen, argon or a hydrogen-argon mixture, preferably argon, and the gas flow rate is 0.1-1L / min, preferably 1L / min; the annealing temperature is 200-1500°C, preferably 600°C, the heating rate is 1-20°C / min, preferably 5°C / min, and the annealing time is 0.5-10h, preferably 2h.
[0019] In the process of mixing the sulfide with the porous carbon, the sulfide can be directly selected from the above-mentioned sulfides, or the sulfide can be prepared by mixing and heat treating a sulfur source and a transition metal salt in a high boiling point solvent, wherein the sulfur source is sulfur powder, thiourea or cysteine, preferably thiourea; the transition metal salt is a cobalt source, and the cobalt source is cobalt chloride, cobalt nitrate or cobalt acetate, preferably cobalt chloride; the high boiling point solvent is ethylene glycol, dimethylformamide, ethylene glycol monomethyl ether, butanol, octanol or octyl acetate, preferably ethylene glycol; the heat treatment temperature is 80-300°C, preferably 150°C, the reaction time is 12-24h, preferably 12h, the heating method is hydrothermal, water bath or oil bath, preferably oil bath; the stirring method is magnetic stirring, and the stirring speed is 0-1500rpm, preferably 300rpm.
[0020] The present invention also provides a membrane modification material, which is obtained by mixing the composite material with a conductive agent, a binder and a solvent, and grinding the mixture into a slurry.
[0021] As a preferred embodiment, the conductive agent is at least one of Super-P, superconducting carbon black, acetylene black, and Ketjen black, preferably Super-P; the binder is at least one of polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR), preferably polyvinylidene fluoride; the solvent is at least one of ultrapure water, N-methylpyrrolidone (NMP), and ethanol, preferably N-methylpyrrolidone; the mass ratio of the composite material to the conductive agent and the binder is 8:1:1, and the mass of the solvent is 1-10 times the total mass of the composite material, the conductive agent, and the binder, preferably 5 times.
[0022] The present invention also provides an application of a diaphragm modification material, wherein the diaphragm modification material is compounded on the surface of a diaphragm and dried to obtain a diaphragm modification layer, and the diaphragm modification layer is applied to secondary batteries, wherein the secondary batteries are mainly lithium-sulfur batteries, sodium-sulfur batteries, and other types of lithium-ion batteries, lithium metal batteries, sodium-ion batteries, etc.; the operating temperature of the secondary battery is -20-80°C, preferably 25°C.
[0023] Among them, the material of the diaphragm is polyethylene, polypropylene, glass fiber or cellulose, preferably polypropylene, the number of layers of the diaphragm is 1-3 layers, preferably 1 layer, the diameter of the diaphragm is 10-50mm, preferably 12-19mm, and most preferably 19mm; the composite process of the diaphragm modification material and the diaphragm is scraping, spraying, spin coating, preferably scraping; the drying method is vacuum drying, freeze drying or air drying, preferably air drying, the drying temperature is 25-200°C, preferably 50°C; the thickness of the diaphragm modification material after drying is 1-100μm, preferably 15μm.
[0024] The present invention has the following advantages:
[0025] (1) The present invention can realize the high-value utilization of agricultural waste, solve the environmental pollution problems derived from improper disposal methods, and generate considerable economic benefits. Existing products converted from agricultural waste have disadvantages such as low added value and poor quality. The present invention converts agricultural waste into porous carbon with a high specific surface area and uses it as a catalyst carrier, so that the performance advantages of biomass itself are effectively utilized, which has great economic benefits.
[0026] (2) The porous carbon of the present invention has a simple preparation process. Compared with traditional catalyst carriers such as graphene and carbon nanotubes, the porous carbon prepared by this method has a significant cost advantage. It can be directly obtained by a two-step carbonization-activation method or a one-step biomass activation method, and has the potential for expanded production. After loading sulfide, its catalytic performance is further improved.
[0027] (3) The porous carbon obtained by the two-step carbonization-activation method or direct activation of biomass has the remarkable feature of high specific surface area. The doping of the original non-carbon elements improves its intrinsic adsorption capacity and catalytic activity. During the heat treatment process of the sulfide loading, its high specific surface area provides a good place for the growth of crystals, improving its dispersibility and catalytic activity. It effectively inhibits the deactivation of the catalyst due to agglomeration or adsorption of a large amount of polysulfide ions, provides a larger reaction interface for the conversion of polysulfide ions, and effectively anchors dissolved polysulfide ions to accelerate their catalytic conversion efficiency.
[0028] (4) Compared with other types of carriers, the porous carbon also makes a greater contribution to the anchoring and conversion of polysulfides. First, during the pyrolysis process, the graphitization degree of the porous carbon increases, which is beneficial to improve the defect of poor conductivity of elemental sulfur and its discharge products. Second, biomass itself has a large amount of non-carbon elements, which can assist in the construction of a beneficial structure of porous carbon during the carbonization-activation process. Polar heteroatoms are mainly beneficial to improving the catalytic performance of porous carbon, and metal salts are mainly helpful to improve the graphitization degree of the material. Third, during the activation process, a large number of micropores, mesopores, and macropores are generated on the surface of the carbon material, which is beneficial to fix polysulfides by physical action and facilitate the rapid transmission of ions. Fourth, the membrane modification layer has a large specific surface area, rich active sites, and light weight, which will not significantly increase the total mass of the battery.
[0029] (5) The porous carbon loaded with metal sulfides prepared by the present invention can be mixed with a conductive agent, a binder, and a solvent, and then a membrane modification layer can be obtained by simply grinding and coating it on a commercial membrane. It is suitable for mass production. Combined with its stabilizing effect on the negative electrode of the battery, its application field can be further extended to lithium-ion batteries, sodium-ion batteries, other types of lithium metal batteries, etc. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The transmission electron microscopy image of the fungus residue-derived porous carbon prepared by the carbonization-potassium hydroxide activation method;
[0031] Figure 2 The transmission electron micrograph of silkworm excrement-derived porous carbon prepared by carbonization-potassium hydroxide activation method;
[0032] Figure 3 The scanning electron micrograph of the silkworm excrement-derived porous carbon loaded with cobalt sulfide;
[0033] Figure 4 The charge and discharge curves of lithium-sulfur batteries assembled with different separators at 0.2C;
[0034] Figure 5 Long cycle diagram of lithium-sulfur batteries assembled with different separators at 0.2C;
[0035] Figure 60.5mA / cm 2 Constant current charge and discharge curves of lithium||lithium symmetric batteries assembled using different separators at different current densities.
[0036] Figure 7 This is the nitrogen adsorption-desorption isotherm diagram of fungus residue carbon activated by 0.3 M potassium ferrate. DETAILED DESCRIPTION
[0037] The present invention is further described below in conjunction with embodiments and drawings.
[0038] Embodiment 1:
[0039] The agricultural and forestry waste described in this embodiment is silkworm excrement, and the silkworm excrement selected is only one kind of agricultural waste. If there are requirements for the structure and elemental composition of the biomass itself, the corresponding agricultural waste can be selected. The cobalt dichloride described in this embodiment is only one of the loaded substances, and other types of catalysts can be loaded on the porous carbon carrier according to the characteristics of the reaction to be catalyzed. The method of this embodiment can also be applied to the disposal of other organic solid wastes, and the application field of its products can also be expanded to the development of other types of secondary battery devices and non-energy storage fields that require carbon materials.
[0040] Constructing a membrane-modified interlayer is considered to be an effective way to suppress the shuttle effect, and cobalt disulfide is a catalytic species widely used in the interlayer, which has a strong affinity with polysulfides. However, cobalt disulfide has poor conductivity (6.7×10 3 S / cm, 300K) makes it unable to effectively mediate the electron transfer process during the redox reaction of the sulfur positive electrode, and cobalt disulfide is prone to agglomeration during the charge and discharge process, so that its catalytic activity decreases significantly with the increase of the number of cycles.
[0041] In order to improve the above problems, the following measures are taken in this embodiment: the silkworm excrement biomass raw material is washed with ultrapure water to remove excess impurities on the surface, and the dried biomass raw material is placed in a tubular furnace under an argon atmosphere, heated to 500°C at a heating rate of 5°C / min, and kept warm for 1 hour. After the material is cooled to room temperature, the carbonized silkworm excrement and potassium hydroxide powder (mass ratio = 1:4) are taken and ground evenly in a mortar to fully mix the two, and then placed in a tubular furnace and heated to 800°C at 3°C / min under an Ar atmosphere, and kept warm for 3 hours. The cooled product is transferred to a beaker, and dilute hydrochloric acid is slowly added while stirring until the solution becomes acidic. After stirring at room temperature for 12 hours, the activated material is filtered with distilled water to neutrality, and then placed in an 80°C blast oven for drying. The structural characteristics of the material are shown in the attached Figure 2 .
[0042] Take 242mg CoCl2·6H2O, 170mg thiourea and 150mg silkworm feces carbon, add them to 70mL ethylene glycol solution, oil bath at 150℃, maintain 300rpm magnetic stirring, heat for 12h, cool, filter and dry. The dried sample is annealed at 600℃ for 2h at a heating rate of 5℃ / min under argon atmosphere to prepare a composite material. The structural characteristics of the material are shown in the attached Figure 3 .
[0043] The composite material, acetylene black and polyvinylidene fluoride were weighed in a mass ratio of 8:1:1, and an appropriate amount of N-methylpyrrolidone was added and ground evenly in a mortar. The slurry was then coated on the surface of the commercial diaphragm with a scraper, and the coated diaphragm was placed in an oven at 50°C for drying and sliced into discs with a diameter of 19 mm. After matching the sulfur positive electrode and lithium negative electrode loaded on CMK-3, a button lithium-sulfur battery was assembled. Battery performance is shown in the attached Figure 4-6 .
[0044] Embodiment 2:
[0045] The orange peel biomass material was washed with ultrapure water to remove excess impurities on the surface and crushed. The dried biomass material was placed in a tube furnace and heated to 500°C at a heating rate of 5°C / min in an argon atmosphere for 1 hour. After the material cooled to room temperature, the carbonized orange peel and potassium hydroxide powder (mass ratio = 1:4) were ground evenly in a mortar to mix the two thoroughly, and then placed in a tube furnace and heated to 800°C at 5°C / min in an Ar atmosphere for 2 hours. The cooled product was transferred to a beaker, and dilute hydrochloric acid was slowly added while stirring until the solution became acidic. After stirring at room temperature for 12 hours, the activated material was filtered with distilled water to neutrality, and then placed in an 80°C blast oven for drying.
[0046] The other steps are the same as in Example 1.
[0047] Embodiment 3:
[0048] The mushroom residue biomass material (solid waste after mushroom cultivation) was washed with ultrapure water to remove excess impurities on the surface, soaked in dilute hydrochloric acid with a mass concentration of 10wt% for 24h to remove impurities, then rinsed with ultrapure water until neutral and dried. The dried biomass material was placed in a tube furnace under an argon atmosphere and heated to 500℃ at a heating rate of 3℃ / min, and kept warm for 1h. After the material cooled to room temperature, the carbonized mushroom residue and potassium hydroxide powder (mass ratio = 1:4) were mixed thoroughly in a container, and then placed in a tube furnace and heated to 800℃ at 3℃ / min under an Ar atmosphere, and kept warm for 3h. The cooled product was transferred to a beaker, and dilute hydrochloric acid was slowly added while stirring until the solution became acidic. After stirring at room temperature for 12h, the activated material was filtered with distilled water to neutrality, and then placed in an 80℃ forced air oven for drying. The structural characteristics of the material are shown in the attached Figure 1 .
[0049] Take 291 mg of cobalt nitrate hexahydrate, 64 mg of sulfur powder and 150 mg of fungus residue carbon, add them to 70 mL of ethylene glycol solution, oil bath at 150 ° C, maintain 300 rpm magnetic stirring, heat for 12 hours, cool, filter and dry. The dried sample is annealed at 600 ° C for 2 hours at a heating rate of 5 ° C / min in an argon atmosphere to prepare a composite material.
[0050] The other steps are the same as in Example 1.
[0051] Embodiment 4:
[0052] The same as Example 1, except that the sulfide supported by the porous carbon is manganese sulfide.
[0053] 170 mg of MnSO4·5H2O was dissolved in a mixed solution of 8 mL of ethanol and 12 mL of water, and then 170 mg of silkworm excrement porous carbon was added, and magnetic stirring was maintained at 300 rpm for 10 h at room temperature, and then dried. The dried material was annealed at 600°C for 2 h at a heating rate of 5°C / min under an argon atmosphere to prepare a porous carbon composite material loaded with manganese sulfide. The other steps were the same as in Example 1.
[0054] Embodiment 5:
[0055] The same as Example 1, the difference is that the obtained diaphragm modification layer is applied to other lithium metal batteries, and the positive electrode material is a single element such as selenium and iodine located in the sixth main group or the seventh main group of the periodic table. Taking lithium-selenium batteries and lithium-iodine batteries as examples, the main problems of the shuttling of polyselenide and polyiodide of the discharge intermediate products are solved, the overall conductivity of the positive electrode material is improved, and the side reaction with the lithium metal negative electrode is prevented, causing the rapid decay of capacity. At the same time, because the material has a certain rigidity, it can prevent dendrites from piercing the diaphragm and causing a short circuit in the battery. The diaphragm modification layer is located on one side or both sides of the diaphragm.
[0056] The other steps are the same as in Example 1.
[0057] Embodiment 6:
[0058] The same as Example 1, except that the obtained diaphragm modification layer is applied to lithium-ion batteries, and the positive electrode materials are lithium iron phosphate, lithium cobalt oxide, lithium nickel oxide and lithium manganese oxide (lithium aluminum oxide) and their ternary composite materials. Its main functions are: improving the wettability of the diaphragm and the electrolyte, uniform lithium ion flux, preventing the negative electrode from producing lithium precipitation, inhibiting the growth of lithium dendrites, and preventing dendrites from piercing the diaphragm. The diaphragm modification layer is located on one side or both sides of the diaphragm.
[0059] The other steps are the same as in Example 1.
[0060] Embodiment 7:
[0061] The same as Example 1, except that the obtained diaphragm modification layer is applied to sodium ion batteries. x MO2 (M is transition metal elements such as Fe, Co, Ni, Mn, Cr, Ti, etc.), Na x M[M'(CN)6]y·zH2O, (M and M' are transition metals such as Fe, Co, Ni, Mn, Cu, Zn, etc.), polyanion positive electrode (sodium iron sulfate, sodium vanadium fluorophosphate and sodium vanadium phosphate), etc., its main functions are: improving the wettability of the diaphragm and the electrolyte, uniform sodium ion flux, preventing the negative electrode from producing sodium precipitation, promoting the reversible storage of sodium ions, inhibiting the growth of sodium dendrites, and preventing dendrites from piercing the diaphragm. The diaphragm modification layer is located on one side or both sides of the diaphragm.
[0062] The other steps are the same as in Example 1.
[0063] Embodiment 8:
[0064] The same as Example 1, except that the obtained diaphragm modification layer is applied to (room temperature) sodium-sulfur batteries, sodium-selenium batteries or sodium-iodine batteries. It mainly solves the shuttling problem of discharge intermediate products polysulfide, polyselenide and polyiodide, and prevents them from having side reactions with the sodium metal negative electrode, causing rapid capacity decay. When applied to high-temperature sodium-sulfur batteries, since the carbon material has good thermal stability, the heat resistance of the diaphragm material can be improved to maintain the stable operation of the battery. The diaphragm modification layer is located on one side or both sides of the diaphragm.
[0065] The other steps are the same as in Example 1.
[0066] Embodiment 9:
[0067] The same as Example 3, except that the obtained porous carbon is activated by potassium ferrate. The other steps are the same as Example 3.
[0068] The fungus residue biomass raw material was washed with ultrapure water to remove excess impurities on the surface, soaked in dilute hydrochloric acid with a mass concentration of 10wt% for 24h to remove impurities, then rinsed with ultrapure water until neutral and dried, and the dried biomass raw material was placed in a tube furnace under an argon atmosphere, heated to 500°C at a heating rate of 5°C / min, and kept warm for 1h. After the material was cooled to room temperature, the carbonized fungus residue and potassium ferrate solution (0.3M) were taken in a container and fully mixed, and an appropriate amount of distilled water was added and stirred for 12h. After drying at 80°C, it was placed in a tube furnace and heated to 800°C at 5°C / min in an Ar atmosphere, and kept warm for 2h. The cooled product was transferred to a beaker, and dilute hydrochloric acid was slowly added dropwise while stirring until the solution became acidic. After stirring at room temperature for 12 hours, hydrochloric acid and sodium hydroxide solutions were used to wash alternately until the filtrate was colorless. The material was filtered with distilled water until it was neutral, and then placed in an 80°C forced air oven for drying. The nitrogen adsorption-desorption isotherm of the obtained material is shown in the attached figure. Figure 7 After the test, the instrument calculated the specific surface area of the material according to the BET formula to be 1911.8m 2 / g.
[0069] Comparative Example 1:
[0070] The same as Example 1, except that the biomass is not subjected to potassium hydroxide activation treatment. The other steps are the same as Example 1. The pore-forming effect of potassium hydroxide is mainly achieved by converting carbon-containing substances (amorphous carbon, methyl, methine, etc.) into carbon monoxide under high temperature conditions. The specific reaction is as follows:
[0071] 6KOH+2C=2K+3H2+2K2CO3
[0072] K2CO3=K2O+CO2
[0073] CO2+C=2CO
[0074] K2CO3+2C=2K+3CO
[0075] K2O+C=2K+CO
[0076] Therefore, the porosity and specific surface area of the carbon material obtained by direct pyrolysis without adding an activating agent are low, and it cannot provide a large adsorption reaction interface, so its ability to adsorb other substances and load metal catalysts is reduced.
[0077] Comparative Example 2:
[0078] The same as Example 1, except that the obtained porous carbon was directly applied to the lithium-sulfur battery separator modification layer without cobalt sulfide loading, and the other steps were the same as Example 1. The battery performance is shown in the attached Figure 5 .
[0079] In summary, the present invention uses the carbonization-activation method to prepare high specific surface area activated carbon, which is a good barrier to block the shuttling of polysulfides. Compared with other methods for preparing activated carbon, the activated carbon produced by this method is partially graphitized amorphous carbon with a maximum specific surface area of >3000m 2 / g. This method is a universal method for producing high specific surface area porous carbon using agricultural waste, which has promotion significance. After loading about 10% sulfide, the specific surface area can be maintained at about 2000m 2 / g, which ensures the efficient transmission of lithium ions in the electrolyte and can effectively anchor polysulfides (attached Figure 4 ). At the same time, it is also possible to expand its application in the field of supported catalysts by loading other types of transition metal salt nanoparticles.
[0080] The porous carbon prepared from agricultural waste and loaded with cobalt sulfide is applied to the diaphragm modification layer of the lithium-sulfur battery, which can effectively inhibit the shuttle effect during the charge and discharge process and accelerate the redox kinetics of the charge and discharge reaction, thereby improving the specific capacity and cycle stability of the lithium-sulfur battery. In previous studies, the initial capacity of the lithium-sulfur battery using ordinary polypropylene diaphragms was about 1200 mAh / g. After the porous carbon loaded with cobalt sulfide in the present invention is used, the sulfur loading is about 1.6 mg / cm 2 When the first cycle capacity is 0.2C, it can reach more than 1500mAh / g (attached Figure 4-5 In addition, since the diaphragm modification layer has the advantages of improving electrolyte wettability, promoting ion conduction, and uniform ion flux, it can improve the problem of dendrite growth in metal batteries and has certain application value in lithium-ion batteries, lithium metal batteries, sodium-ion batteries, and sodium metal batteries (see Appendix Figure 6 ).
Claims
1. A membrane modification material, characterized in that: The composite material is mixed with a conductive agent, a binder, and a solvent A, and ground into a slurry to obtain a diaphragm modification material; The composite material is prepared by mixing porous carbon with CoCl2•6H2O and thiourea in solvent B, and then vacuum filtering the mixture, drying the filter residue, and annealing under the protection of an inert gas to obtain a porous carbon-sulfide composite material; The porous carbon is prepared by using silkworm excrement as biomass material, mixing the biomass material with an activator and placing it in a reaction vessel, and performing activation heat treatment under the protection of an inert gas to obtain the porous carbon; The activator is at least one of zinc chloride, phosphoric acid, potassium ferrate, potassium hydroxide, ferric chloride, ferric nitrate and water vapor.
2. A membrane modification material according to claim 1, characterized in that: The mass ratio of the biomass material to the activator is 1:0.1-6; the inert gas in the activation heat treatment is nitrogen, argon or a hydrogen-argon mixture, and the flow rate of the inert gas is 0.1-2 L / min; the temperature of the activation heat treatment is 200-1500°C, the heating rate is 1-20°C / min, and the activation heat treatment time is 0.5-10 h.
3. A membrane modification material according to claim 1, characterized in that: The biomass material needs to be pretreated, and the pretreatment steps are cleaning and drying; The cleaning is at least one of water washing, hydrochloric acid washing, sulfuric acid washing, nitric acid washing, hydrofluoric acid washing, sodium hydroxide washing, potassium hydroxide alkaline washing, and ethanol washing; The drying temperature is 40-150° C., and the drying time is 6-72 h.
4. A membrane modification material according to claim 3, characterized in that: The dried biomass material is further crushed and sieved, and the powder particle size after crushing is 50-400 mesh.
5. A membrane modification material according to claim 3, characterized in that: The pretreated biomass material needs to be pre-carbonized and heat treated under the protection of an inert gas before being mixed with the activator; Wherein, the inert gas is nitrogen, argon or a hydrogen-argon mixture; the flow rate of the inert gas is 0.1-1L / min; the temperature of the pre-carbonization heat treatment is 200-1500°C, the heating rate is 1-20°C / min, and the pre-carbonization heat treatment time is 0.5-10h.
6. A membrane modification material according to claim 1, characterized in that: The solvent B is ethanol, ethylene glycol, dimethylformamide, ethylene glycol monomethyl ether, butanol, octanol or octyl acetate; the inert gas in the annealing treatment is nitrogen, argon or a hydrogen-argon mixture, and the gas flow rate is 0.1-1 L / min; the annealing temperature is 200-1500°C, the heating rate is 1-20°C / min, and the annealing time is 0.5-10 h.
7. The membrane modification material according to claim 1, characterized in that: The conductive agent is at least one of Super-P, superconducting carbon black, acetylene black, and Ketjen black; the binder is at least one of polyvinylidene fluoride, sodium carboxymethyl cellulose, and styrene-butadiene rubber; the solvent A is at least one of ultrapure water, N-methylpyrrolidone, and ethanol; the mass ratio of the composite material to the conductive agent and the binder is 8:1:1, and the mass of the solvent A is 1-10 times the total mass of the composite material, the conductive agent, and the binder.
8. An application of the membrane modification material according to claim 1, wherein the membrane modification material is compounded on the surface of the membrane and dried to obtain a membrane modification layer, and the membrane modification layer is applied to a secondary battery; in, The material of the diaphragm is polyethylene, polypropylene, glass fiber or cellulose, the number of layers of the diaphragm is 1-3, and the diameter of the diaphragm is 10-50 mm; the composite process of the diaphragm modification material and the diaphragm is scraping, spraying, and spin coating; the drying method is vacuum drying, freeze drying or blast drying, and the drying temperature is 25-200°C; the thickness of the diaphragm modification material after drying is 1-100 μm.
Citation Information
Patent Citations
A composite electrode material of porous hollow carbon spheres loaded with tin sulfide nano quantum dots
CN108987735A
Battery diaphragm and preparation method thereof, and lithium-sulfur battery
CN112117417A